A volcanic CO2 pulse triggered the Cretaceous oceanic Anoxic event 1a and a biocalcification crisis - S. Méhay; C. E. Keller; S. M. Bermasconi; H. Weissert; P. A. Hochuli; E. Erba; C. Bottini (Geology, 2009)
The Aptian Oceanic Anoxic Event 1a (OAE1a, ca.120 Ma ago) is one of the most prominent of a series of geologically brief intervals in the Cretaceous characterized by the deposition of organic carbon-rich sediments. OAEs refl ect major perturbations in the global carbon cycle evidenced by sedimentary carbon isotope records. However, the triggering mechanisms for OAEs remain controversial. Here we present a bulk-rock and molecular (marine and terrestrial biomarkers) C isotope record at unprecedented time resolution, from the Cismon section of northern Italy, that shows that OAE1a conditions were reached over a period of several thousands of years through a stepwise perturbation of the carbon cycle. The documented sequence of events is most compatible with a trigger associated with increased CO2 emissions, possibly leading to a doubling of pCO2, which in turn caused larger C isotope fractionation in marine and terrestrial organisms, and a major biotic crisis in the calcareous nannoplankton. Our data also show that a release of isotopically light carbon from partial methane hydrate dissociation probably played a minor role in the OAE1a carbon cycle perturbation.